2021
DOI: 10.31332/ijtk.v2i1.3
|View full text |Cite
|
Sign up to set email alerts
|

EFL Students’ Perceptions of The Benefits of Project-Based Learning in Translation Class

Abstract: This study aims to describe students’ perceptions of the benefits of project-based learning in translation class. The project focuses on the students’ perceptions and the benefits of translation project. The research method uses a qualitative approach with descriptive data analysis technique. The participants of this study consist of 25 university students. The qualitative data were analyzed by questionnaire and students’ reflection adopted from Siregar (2018). The results of the research revealed that the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Learning models that emphasize the active role of students such as this project-based learning model can in turn help Peacesantren Welas Asih to produce graduates who not only have good scientific and moral competence, but are also able to contribute in an actual way through problem solving skills and innovation. This is consistent with the advantages of implementing a project-based learning model that is able to foster creativity, the ability to cooperate, independence, the use of technology, to destroy barriers that hinder learning (Scarbrough et al, 2004;Boss & Krauss, 2015;Sathappan & Gurusamy, 2021;Astuti et al, 2021).…”
Section: Internalization Of Peace Values Through Curriculum and Learn...supporting
confidence: 63%
“…Learning models that emphasize the active role of students such as this project-based learning model can in turn help Peacesantren Welas Asih to produce graduates who not only have good scientific and moral competence, but are also able to contribute in an actual way through problem solving skills and innovation. This is consistent with the advantages of implementing a project-based learning model that is able to foster creativity, the ability to cooperate, independence, the use of technology, to destroy barriers that hinder learning (Scarbrough et al, 2004;Boss & Krauss, 2015;Sathappan & Gurusamy, 2021;Astuti et al, 2021).…”
Section: Internalization Of Peace Values Through Curriculum and Learn...supporting
confidence: 63%
“…With the challenges that traditional assessment presented, many teachers (with support from administration), found that authentic assessment worked well in the online format. Teachers suggested they capitalized in part on the established benefits of project-based learning (Aldabbus, 2018;Astuti et al, 2021). In the focus group one participant suggested, "Project-based learning is a more authentic learning experience for the students.…”
Section: Options To Mitigate Negative Impactsmentioning
confidence: 99%